2016
DOI: 10.5194/acp-16-759-2016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shipping emissions on air pollution in the greater North Sea region – Part 2: Scenarios for 2030

Abstract: Abstract. Scenarios for future shipping emissions in the North Sea have been developed in the framework of the Clean North Sea Shipping project. The effects of changing NO x and SO 2 emissions were investigated with the CMAQ chemistry transport model for the year 2030 in the North Sea area. It has been found that, compared to today, the contribution of shipping to the NO 2 and O 3 concentrations will increase due to the expected enhanced traffic by more than 20 and 5 %, respectively, by 2030 if no regulation f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…They have also shown that the strengthened limit on the fuel S content in 2015 from 1.0 % to 0.10 % brought a significant decrease in emissions as well as contributions of shipping to air pollution by SO2 and to S deposition (maximum contribution about 2 %) and to a reduction of shipping contribution to the concentrations of PM. Aulinger et al (2016) and Matthias et al (2016) studied impacts of the current and future (2030) North Sea shipping on air pollution and found contributions consistent with Jonson et al (2019) (highest NO2 contributions 25 % 130 and 15 % in summer and winter, respectively, ozone increased by 10% along Scandinavian coast). By 2030, the contribution of shipping to the NO2 and O3 concentrations was estimated to increase by more than 20 % and 5 %, respectively, due to the expected enhanced traffic, if no regulation for further emission reductions is implemented in the North Sea area .…”
Section: Introductionsupporting
confidence: 69%
“…They have also shown that the strengthened limit on the fuel S content in 2015 from 1.0 % to 0.10 % brought a significant decrease in emissions as well as contributions of shipping to air pollution by SO2 and to S deposition (maximum contribution about 2 %) and to a reduction of shipping contribution to the concentrations of PM. Aulinger et al (2016) and Matthias et al (2016) studied impacts of the current and future (2030) North Sea shipping on air pollution and found contributions consistent with Jonson et al (2019) (highest NO2 contributions 25 % 130 and 15 % in summer and winter, respectively, ozone increased by 10% along Scandinavian coast). By 2030, the contribution of shipping to the NO2 and O3 concentrations was estimated to increase by more than 20 % and 5 %, respectively, due to the expected enhanced traffic, if no regulation for further emission reductions is implemented in the North Sea area .…”
Section: Introductionsupporting
confidence: 69%
“…The greatest benefit of an advanced bottom-up approach like the one presented here is the possibility to use it for creating and evaluating sophisticated emission scenarios (Matthias et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We apply the MECO(n) (MESSy-fied ECHAM and COSMO models nested n times; e.g. Kerkweg and Jöckel, 2012b;Mertens et al, 2016) model system together with a detailed source apportionment method (tagging; Grewe et al, 2017). This model system couples, during runtime, the global chemistry-climate model EMAC (ECHAM5/MESSy for Atmospheric Chemistry; Jöckel et al, 2006Jöckel et al, , 2010 with the regional chemistry-climate model COSMO-CLM/MESSy (Kerkweg and Jöckel, 2012a), which consists of the COSMO-CLM model equipped with the MESSy (Modular Earth Submodel System; Jöckel et al, 2005Jöckel et al, , 2010 infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…More details about the MECO(n) model system are presented in a set of publications including a chemical and meteorological evaluation (Kerkweg and Jöckel, 2012a, b;Hofmann et al, 2012;Mertens et al, 2016;and Kerkweg et al, 2018). The set-up of the simulation applied in the present study is very similar to that described by Mertens et al (2016). Therefore, we only present the most important details of the model set-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation